Optimization of Inventory Management through the 5S Methodology for Cost Reduction in a Microenterprise of the Mining-Industrial Sector - Cardenas Diaz, Danny Miguel; Villegas Cubas, Dayana Rouss; Polo Herrera, Kelly Milena; Díaz Díaz, Marco Antonio (LACCEI, 2025)
The study addresses the application of the 5S methodology to improve inventory management in a company dedicated to the commercialization of mining products. Issues identified included warehouse disorganization, difficulty locating materials, unnecessary overstock, and high operational costs. To tackle these problems, an improvement plan was designed based on the five stages of the 5S methodology: sort, set in order, shine, standardize, and sustain. The actions implemented included the formation of a 5S committee, staff training, labeling of shelves, zoning, cleaning stations, and internal audits. After execution, the company achieved greater organization, reduced search times, improved product visibility, and decreased operational costs. The benefits allowed for a short-term return on investment and created a more efficient work environment. The results validate the effectiveness of 5S as an accessible, practical, and sustainable tool for optimizing logistical processes in small companies within the industrial sector.